Pengaruh Intensitas Konsumsi Energi (IKE) Dan Akses Air Bagi Produk Domestik Bruto Negara-Negara Organisasi Kerjasama Islam (OKI) - Bagus Wilarnugroho; Sri Herianingrum (Universitas Airlangga, 2016)
Energy use intensity (EUI) and water access are vital to economic activities. World energy need is growing meanwhile the energy resource couldn’t follow it. Futhermore, world fresh water quantity is declining.This research is aim to acknowledge whether there is an impact of EUI and water access on gross domestic products (GDP) in Organization of Islamic Cooperation (OIC) member states. The research is using World Bank data with quantitative approach. The data had been running using panel data regression method. The data are from Indonesia, Malaysia, Pakistan and Bangladesh which consist of EUI and water access data as an independent variables and GDP as a dependent varible. According to the results, seen that EUI and water access have a sigificant impact, partialy and simultaneously, to GDP within four OIC member. Therefore, we can conclude that the EUI and water access are able to increase GDPof OIC member states.